2020
DOI: 10.1038/s41598-020-57879-x
|View full text |Cite
|
Sign up to set email alerts
|

Prey and predator overlap at the edge of a mesoscale eddy: fine-scale, in-situ distributions to inform our understanding of oceanographic processes

Abstract: Eddies can enhance primary as well as secondary production, creating a diverse meso-and submesoscale seascape at the eddy front which can affect the aggregation of plankton and particles. Due to the coarse resolution provided by sampling with plankton nets, our knowledge of plankton distributions at these edges is limited. We used a towed, undulating underwater imaging system to investigate the physical and biological drivers of zoo-and ichthyoplankton aggregations at the edge of a decaying mesoscale eddy (ME)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 79 publications
0
55
0
Order By: Relevance
“…10-100 km) physical features [10,11]. Mesoscale eddies can provide physical mechanisms to transport [12] or aggregate prey [13], thereby providing foraging opportunities for wide-ranging marine predators, from seabirds to sharks [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…10-100 km) physical features [10,11]. Mesoscale eddies can provide physical mechanisms to transport [12] or aggregate prey [13], thereby providing foraging opportunities for wide-ranging marine predators, from seabirds to sharks [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Underwater plankton imaging has the capacity to detect patterns of the plankton distributions that we would be unable to be tackled by sampling with nets. [21]. Therefore, we consider applying machine vision technology to underwater images or videos is currently a feasible method for studying plankton.…”
Section: Introductionmentioning
confidence: 99%
“…There have been numerous studies which have identified areas of front persistence, or high front frequency (for example see [5,15]), as regions of enhanced regional biodiversity, and species abundance. Their surface expressions, which are the only features detectable using satellite sensors, represent far more extensive structures beneath the surface, shaping the distribution of life beneath the surface [16][17][18], and driving the region's ecosystem functioning [6]. STH features vary regionally.…”
Section: Introduction 1heterogeneity and The Ocean-surfacementioning
confidence: 99%